High-performance GeSn photodetector and fin field-effect transistor (FinFET) on an advanced GeSn-on-insulator platform - Wang, Wei (2019)
We report the first demonstration of high-performance GeSn metal-semiconductor-metal (MSM) photodetector and GeSn p-type fin field-effect transistor (pFinFET) on an advanced GeSn-on-insulator (GeSnOI) platform by complementary metal-oxide-semiconductor (CMOS) compatible processes. The detection range of GeSn photodetector is extended beyond 2 µm, with responsivities of 0.39 and 0.10 A/W at 1550 nm and 2003 nm, respectively. Through the insertion of an ultrathin Al2O3 Schottky-barrier-enhancement layer, the dark current IDark of the GeSn photodetector is suppressed by more than 2 orders of magnitude. An impressive IDark of ~65 nA was achieved at an operating voltage of 1.0 V. A frequency response measurement reveals the achievement of a 3-dB bandwidth of ~1.4 GHz at an illumination wavelength of 2 µm. GeSn pFinFET with fin width (Wfin) scaled down to 15 nm was also fabricated on the GeSnOI platform, exhibiting a small subthreshold swing (S) of 93 mV/decade, a high drive current of 176 µA/µm, and good control of short channel effects (SCEs). This work paves the way for realizing compact, low-cost, and multi-functional GeSn-on-insulator opto-electronic integrated circuits.